1. Biennale der europäischen Grafik Heidelberg 1979. - 1. Biennale der europäischen Grafik Heidelberg 1979 (Heidelberg : Biennale Heidelberg e.V., 1979)
Alechinsky, Pierre ; Coulon, Jean ; Leonard, Michèle ; Mara, Pol ; Raveel, Roger ; Somville, Roger ; Winance, Alain ; Krassimira, Drenska ; Panayotov, Todor ; Stoev, Borislav ; Dieter, Asmus ; Martin, Erhardt Hans ; Grüger, Ev ; Kriwet, Ferdinand ; Nagel, Peter ; Piegelbrock, Jürgen ; Schumacher, Emil ; StOrtenbecker, Nikolaus ; Wunderlich, Paul ; Herold, Rainer ; Münzner, Rolf ; Wittig, Werner ; Nuoreva, Marjatta ; Diaz, Gérard ; Friedlaender, Johnny ; Kwasniewska, Barbara ; etc.
1. Biennale der europäischen Grafik Heidelberg 1979
boek